1
2007-01-01 18:50:55
·
answer #1
·
answered by hardcore 2
·
0⤊
2⤋
Well, the gradient of the perpendicular line is equal to -1 divided by 3 = -1/3
Then, you sub in the X and Y values, to give 1 = -1/3*6 + c.
Then you just simplify to give c = 3.
This then gives the equation of the perpendicular as y = -1/3x + 3.
2007-01-02 00:46:39
·
answer #2
·
answered by shoop.dogg 2
·
0⤊
0⤋
let line be y = mx + c where m is slope & m is y intercept
since it passes through (6,1) y =1 & x=6 should satisfy the equation
we get
1 = 6m + c
c =1-6m
therefore new equation is
y = mx + 1 - 6m
since y=3x-1is perpendicular to y = mx + 1 - 6m having slope m
(slope of 1 line)*(slope of 2 line)=-1
3*m = -1
m = -1/3
therefore required equation of line is
y = (-1/3)x + 1-6*(-1/3)
y = (-1/3)x+ 1+2
y = (-1/3)x+3
3y = -x + 9
3y + x = 9
2007-01-01 21:17:02
·
answer #3
·
answered by kainesh p 2
·
0⤊
0⤋
y=3x-1. Find the gradiant which is 3.
If the line is perpendicular then the gradiant is -1/3.
since the line passes through (6,1) the equation is obtained through
(y-1) / (x-6)= -1/3
3y-3 = -x+6
3y+x=9
y= - x / 3 + 3
2007-01-01 18:57:52
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Its pretty easy man...For perpendicular lines the slope of one is the invesre of the other...i.e m(1)=1/m(2).....So in your case the slope of the perp line is -1/3 ya get?
So now you have the slope,you have a point on the line(6,1) you just slap it into the formula y-y(1)=m(x-x(1))....Cool?
Oh and watch your signs!!!
2007-01-02 08:26:31
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
Inverse the gradient of your eqt, ie m=-1/3. Then to get your y intercept sub in your x and y values into your eqt ie 1=-1/3*6+yint yint=1+2=3. So eqt is y = -1/3x+3.
2007-01-01 19:02:14
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
gradient ,m=3
gradient of perpendicular = -1/3
Equation of perpendicular thro` (6,1) is given by:-
y-1= -1/3(x-6)
3y-3=-1(x-6)
3y-3=-x+6
x+3y-9=0
2007-01-01 23:46:39
·
answer #7
·
answered by Como 7
·
0⤊
0⤋
well first you take just the slope and inverse it. (meaning -1/(current slope). so we get -1/3 for that. now y=-(1/3)x is perpandicular but now you gotta get it to go thru that point. so you do:
(y-1)=-(1/3)(x-6)
then just splve for y
y=-(1/3)(x-6)+1
y=-(1/3)x+2+1
y=-(1/3)x+3
2007-01-01 18:52:02
·
answer #8
·
answered by Dashes 6
·
1⤊
0⤋
Your (6,1) is your (x,y) so just plug those numbers into your existing equation. y=3x-1
2007-01-01 18:54:51
·
answer #9
·
answered by dalbana5 2
·
0⤊
2⤋
your a ******* dumbass if u dont get this, how old are you like 13
2007-01-01 18:57:55
·
answer #10
·
answered by Javie 1
·
0⤊
3⤋